Analysis of predictors of adherent perinephric fat and its impact on perioperative outcomes in laparoscopic partial nephrectomy: a retrospective case–control study - Lu Fang (BMC, 2021)
Abstract Background Adherent perinephric fat (APF), characterized by inflammatory fat surrounding the kidney, can limit the isolation of renal tumors and increase the operative difficulty in laparoscopic partial nephrectomy (LPN). The aim of this study was to investigate the predictors of APF and its impact on perioperative outcomes during LPN. Methods A total of 215 consecutive patients undergoing LPN for renal cell carcinoma (RCC) from January 2017 to June 2019 at our institute were included. We divided these patients into two groups according to the presence of APF. Radiographic data were retrospectively collected from preoperative cross-sectional imaging. The perioperative clinical parameters were compared between the two groups. Univariate and multivariate analyses were performed to evaluate the predictive factors of APF. Results APF was identified in 41 patients (19.1%) at the time of LPN. Univariate analysis demonstrated that APF was significantly correlated with the male gender (P = 0.001), higher body mass index (P = 0.002), lower preoperative estimated glomerular filtration rate (P = 0.004), greater posterior perinephric fat thickness (P < 0.001), greater perinephric stranding (P < 0.001), and higher Mayo Adhesive Probability (MAP) score (P < 0.001). The MAP score (P < 0.001) was the only variable that remained an independent predictor for APF in multivariate analysis. We found that patients with APF had longer operative times (P < 0.001), warm ischemia times (P = 0.001), and greater estimated blood loss (P = 0.003) than those without APF. However, there were no significant differences in surgical approach, transfusion rate, length of postoperative stay, complication rate, or surgical margin between the two groups. Conclusions Several specific clinical and radiographic factors including the MAP score can predict APF. The presence of APF is associated with an increased operative time, warm ischemia time, and greater estimated blood loss but has no impact on other perioperative outcomes in LPN.